Reduction zinc by aluminum sulphate and superfloc a-110: laboratory level - Cuadros Oria, Saida Margarita (2020)
This article deals with pollution due to the presence of zinc in the Pajuscocha lake, because mining effluents that are being discharged to the lagoon with an average daily flow rate of approximately 52l/s, exceeding the maximum permissible limits for mining effluents (> 1.5 mg/l). For the purposes of the study, two actions were performed, the first to determine the pH of the flow rate and the zinc concentration of the effluent, allowing to propose a second action related to the formulation of eight samples based on the variables pH, coagulant Aluminum Sulfate Al2(SO4)3.14H2O and Superfloc A-110 flocculant at the laboratory level, cost and benefit were considered for the choice of coagulant and flocculant in order to reduce the zinc concentration of the mining effluent; In addition to its accessibility in the market. Finally, by executing the two actions, the concentration of zinc was reduced to 0,79 mg/l, by means of the conditions: coagulant: 6 ml, flocculant: 1ml and pH: 8,8.